IMPLEMENTATION OF A PROJECT-BASED LEARNING MODEL TO DEVELOP STUDENTS' ABILITY TO DO BUSINESS - Suharsono, Naswan; Hidayat, Rachmad (International Journal of Business, Law, and Education, 2023)
This applied research was conducted to implement a project-based learning (PBL) model with five variations of business management activities and its five components in an integrated manner to improve the ability to run a business. The implementation of this prescriptive model was carried out to improve operational and managerial skills, as well as business development through improving product quality and access to markets.  The research design used was descriptive-exploratory, starting from the selection of the type of business, continuing to the identification of strengths and weaknesses, opportunities and threats, and action plans to turn threats into new business opportunities. The ability to run a business is measured from the aspects of resources, capital, products, markets, and future development programs.  Data on the improvement of managerial and operational skills, as well as data on the business development of the 35 student and alumni entrepreneurs were collected through project assignments and field observations. The efforts to improve the ability to run a business and the ability to capture market opportunities were analyzed by SWOT analysis and component analysis. The results of the analysis show that the ability to find business opportunities and predict future needs for goods and services can be developed through lecture classes, while operational skills and managerial abilities can be improved through the process of interaction with economic business actors in the field.